Deconstructing the Israeli-Palestinian Conflict in Online News Media: A Critical Discourse Analysis - Darojat, Alfainy; Widhiatama, Daniel Ari (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
This study aims to find the representation of the Israeli-Palestinian conflict presented in Al-Jazeera News and BBC News. The data for this study were words and sentences that represent how Al Jazeera News and BBC News reported the Israeli-Palestinian conflict. The data are examined using Fairclough's three-dimensional model. The findings of this study showed that Al Jazeera and BBC News represent the Israeli-Palestinian conflict differently. BBC News represented Hamas as the main actor in the October 7 attacks in Israel and Israeli citizens and soldiers are depicted as victims. Al Jazeera, on the other hand, depicted Hamas as the party responding to Israel's conspiracy against Palestinians, emphasizing a moral commitment to avoid civilian harm and blaming Israeli soldiers and police for civilian casualties.